Prevention of Epstein-Barr virus-induced B-cell outgrowth by interferon alpha. - Garner, J G (1984)
An in vitro system for determining the efficacy of interferon alpha (IFN-alpha) in preventing B-cell outgrowth due to Epstein-Barr virus (EBV) was developed. Unfractionated cord blood mononuclear cells, T-cell-depleted cord blood mononuclear cells, or adult T-cell-depleted mononuclear cells were exposed to IFN-alpha for 18 to 20 h followed by incubation with the B95-8 strain of EBV for 2 h. B-cell outgrowth was monitored by microscopic examination, [3H]thymidine incorporation, and Epstein-Barr nuclear antigen detection. Cell density and viral inoculum both affected the sensitivity of outgrowth to IFN-alpha. IFN-alpha was most effective when added at each feeding after infection as well as before infection with EBV. The mean of the lowest IFN-alpha concentration tested at which transformation failed to occur after infection with the B95-8 strain of EBV at a 50% transforming dose of 10(2.0) to 10(3.0)/ml was similar for unfractionated cord blood mononuclear cells, T-cell-depleted cord blood mononuclear cells, and adult T-cell-depleted mononuclear cells. The B95-8 strain and clinical EBV isolates required similar IFN-alpha concentrations to prevent outgrowth. In this system, IFN-alpha at pharmacologically achievable concentrations prevented EBV-induced B-cell outgrowth. These data indicate that IFN-alpha deserves further study as a potential therapeutic agent for EBV-induced syndromes.